Clinical impact of normal alanine aminotransferase on direct‐acting antiviral outcome in patients with chronic hepatitis C virus infection. Issue 4 (23rd December 2019) - Joshita, Satoru; Sugiura, Ayumi; Umemura, Takeji; Yamazaki, Tomoo; Fujimori, Naoyuki; Matsumoto, Akihiro; Usami, Yoko; Tanaka, Eiji
Abstract : Background and Aims: This study aimed to clarify the clinical picture of hepatitis C virus (HCV) carriers with normal alanine aminotransferase (CNALT) and those with ALT elevation (non‐CNALT) under direct‐acting antivirals (DAAs). Methods: We enrolled 1002 patients with HCV (427 men, median age: 69 years) who had received DAAs for comparisons between CNALT (ALT ≤33 U/L in males and ≤25 U/L in females; n = 374) and non‐CNALT ( n = 628) groups. Results: CNALT patients displayed a higher platelet count (PLT) (170 000 vs 146 000/μL, P < 0.0001) and albumin (4.1 vs 4.1 g/dL, P = 0.0006) but lower AST (25 vs 51 U/L, P < 0.0001), alpha fetoprotein (3.2 vs 5.4 ng/mL, P < 0.0001), and liver fibrosis marker scores (all P < 0.0001). The sustained virologic response rate was comparable between the CNALT and non‐CNALT groups (97.8 vs 95.3%, P = 0.106). The cumulative incidence of hepatocellular carcinoma (HCC) after DAA treatment was comparable between the CNALT and non‐CNALT groups ( P = 0.117, log‐rank test). In CNALT patients with HCC history, PLT ≥150 000/μL was an independent risk factor of HCC recurrence ( P = 0.019). In non‐CNALT patients without HCC history, male gender ( P = 0.021) and albumin <4.0 g/dL ( P = 0.007) were independent risk factors, while PLT < 150 000/μL ( P = 0.081) was a marginal risk factor of HCC occurrence. Conclusion: CNALT patients displayed a milder degree of liver fibrosis. Combinations of CNALT and PLT status might be useful as markers for HCC occurrence or recurrence surveillance. Abstract : Hepatitis C virus carriers with normal alanine aminotransferase displayed milder disease progression under modern direct‐acting antivirals era. Combinations of alanine aminotransferase and platelet count levels might be useful as markers for hepatocellular carcinoma occurrence or recurrence surveillance after direct‐acting antivirals.